STATE ASSESSMENT OF THE INDIVIDUALS WITH POST-TRAUMATIC STRESS DISORDER - Rebryk, Yu. Yu.; Ulianytska, N. Ya.; Andriichuk, O. Ya. (Rehabilitation and Recreation, 2024)
Relevance. Patients with post-traumatic stress disorder manifestations have changes in the following indicators, therefore, to treat patients properly, we need to select and investigate the initial indicators of the health state of these individuals. Aim is to assess the physical and psychological condition of patients with post-traumatic stress disorder. Materials and methods. In our research, analytical methods and a structured analysis of national and foreign literature have been used. 24 young female patients participated in the research. The SF-36 International Quality of Life Questionnaire, the Mississippi Scale for Combat-Related PTSD, and the Hospital Anxiety and Depression Scale (HADS) have been used to conduct the study. Results. According to the results of the Mississippi Scale for Combat-Related PTSD, the participants were divided into three groups – Group A – 5 people without PTSD symptoms, Group B – 13 people with mental disorders, and Group C – 6 people with PTSD symptoms. According to the results of the SF-36 International Quality of Life Questionnaire, we assessed the physical component of health (PCH) and the mental component of health (MCH). Patients with a high level of PCH – 1 person, with an increased level of PCH – 4 people, with an average level of PCH – 13 people, with a low level of PCH – 5 people, with a low level of PCH – 1 person. Patients with a high level of MCH – 0 people, with an increased level of MCH – 3 people, with an average level of MCH – 9 people, with a reduced level of MCH – 10 people, with a low level of MCH – 2 people. According to the results of the HADS questionnaire on the HADS-A scale, 2 people with a normal level of anxiety, 15 people with subclinically expressed anxiety, and 7 people with clinically expressed anxiety have been found. According to the HADS-D scale, 1 person with a normal level of depression, 13 people with subclinically expressed depression, and 10 people with clinically expressed depression have been identified. Conclusion. The results of our study confirm the importance of an integrated study of the physical and mental health of patients with post-traumatic stress disorder and determine the main directions of further scientific and practical research in this area.